Preventing leaders' autocratic entrenchment by exponential super-majority threshold escalators - Shapira, Reuven (Frontiers in Political Science, 2023)
This article focuses on alternatives to leaders' constitutional term limits which failed to protect democracy in innumerable countries as they did not reduce incumbency advantages in reelection contests. Such a reduction can achieve a super-majority thresholds escalator for incumbents' re-election. Research has found that setting super-majority thresholds for leadership offices improves the quality of leadership. However, leaders' autocratic entrenchment poses the worse problem of democratic leadership quality. Setting escalating super-majority thresholds for an incumbent's re-election would bar autocratic entrenchment by reducing her/his incumbency advantages in re-election contests. Both ordinal and exponential escalator versions prolong the tenure of successful high-moral effective leaders beyond two terms, allowing them to use accumulated trust credit to advance radical changes, while incumbents who fail to achieve a super-majority threshold are replaced. However, the ordinal version lacks a terminal term, thus it may not prevent autocratic entrenchment, while the exponential version with its terminal term that ensures succession while escalating supermajority thresholds mitigates the exponential growth of leaders' power resources with tenure.After an incumbent fails to re-elect, a second voting round without her/him will give the winner a clear mandate to rule. Suggestions for further study of barring leaders' entrenchment by exponential escalating super-majority thresholds are offered.